(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Relevance: A comparative study of diagnostic hysteroscopy and ultrasound in the diagnosis of abnormal uterine bleeding in perimenopausal women showed the advantage of diagnostic hysteroscopy over ultrasonic methods of sensitivity, specificity: 81% and 65%, respectively.The aim of the study: Study the structure of the endometrium in women with pathology of reproductive organs.Materials and research methods: 30 womens in perimenopause suffering from abnormal uterine bleeding at the age of 46-49 years. The survey methods were: - general clinical - medical history, objective status, laboratory research methods. Gynecological history and gynecological status. TVS. Curettage of the uterine cavity with subsequent histology hysteroscopy with targeted biopsy.The Results of the Study. Curettage of the uterine cavity with subsequent histology was performed in 29 examined patients with the aim of diagnosing and stopping bleeding. The histology responses were as follows: glandular endometrial hyperplasia in 9 (30%) patients, glandular cystic hyperplasia in 3 (7.5%) patients, endometrial polyposis in 16 (45%), leiomyoma in 1 (2,5%). Conclusions. The histology is considered the most informative method for women with pathology of reproductive organs.